Fake Eggs on the Ghanaian Market: An Emperical Evidence - Shukura Market, Greater Accra Region, Ghana - Benjamin, Bartels; Amina, Hussein; Gadzekpo, Victor Patrick Yao (International Journal of Environment, Agriculture and Biotechnology, 2023)
Background and objectives: In recent times, the Ghanaian media space has news of the proliferation of fake eggs in the market especially in the capital, Accra. The Food and Drugs Authority (FDA) of Ghana, the agency responsible for regulating wholesomeness of food has refuted this assertion after thorough investigations. The issue could affect the contribution of poultry to the economy. The aim of the study therefore is to determine the authenticity of eggs sold in the Ablekuma central sub-metro in the Greater Accra region of Ghana. The results shall contribute to the baseline data on eggs, and to restore consumer confidence in eggs sold in Ghana. Methods: The spectral bands of the shells, albumen and yolk of the egg samples were determined using FTIR analysis, and knowledge about fake eggs through survey. Results: The spectra of the shells, albumin and yolk of the samples corresponded to the standard spectra of authentic egg. The survey revealed lack of knowledge about fake eggs. Conclusion: In spite of the lack of knowledge about fake eggs, the eggs were authentic. This confirms the assertion of FDA of Ghana.